A Methodology for Evaluating Military Systems in a Counterproliferation Role - Stafira, Stanley; Parnell, Gregory S.; Moore, James T. (Management Science, 1997)
This paper illustrates a methodology to evaluate how dissimilar military systems support the accomplishment of the United States' counterproliferation objectives. The key questions in evaluating counterproliferation systems are identified. By using decision analysis, an influence diagram model is developed that represents military activities in the counterproliferation process. A value model is developed that enables systems to be evaluated against common criteria. An analysis of intelligence, defensive, and offensive counterproliferation systems suggests that intelligence system improvements may provide the greatest potential to meet the United States' counterproliferation objectives. Sensitivity analysis is conducted to determine which factors in the model are most important. To demonstrate the model, nine systems from the Air Force Vulcan's Forge 1995 wargame are evaluated. This paper illustrates the value of decision analysis, and influence diagrams in particular, by involving decision makers and subject matter experts in structuring complex problems for analysis.